Content of basic concepts of the Interior Troops construction - Shmakov, О. М. (Honor and Law, 2019)
Concepts of the Interior Troops construction in order to apply them in developing the guiding document – Basics of operational employment of the Interior Troops (Interior Troops Manual) are given.